Asphalt-based composite hard carbon material and preparation method thereof

By mixing asphalt with solvent and embedding solvent molecules into the graphite layer, the problem of graphitization of asphalt-based hard carbon materials during high-temperature carbonization is solved, and the effect of improving the sodium ion diffusion channel and material performance is achieved.

CN119551654APending Publication Date: 2025-03-04GUANGDONG UNIV OF PETROCHEMICAL TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411732764.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Asphalt-based hard carbon materials are easily graphitized during high-temperature carbonization, resulting in difficulty in embedding or removing sodium ions, which in turn affects the sodium storage performance of the material.

Method used

By mixing the asphalt with solvent A and solvent B, and inserting the solvent molecules into the graphite layer by ball milling or soaking, increasing the layer spacing, changing the microstructure of the asphalt, thereby expanding the sodium ion diffusion channel.

Benefits of technology

The reversible specific capacity and cyclic performance of asphalt-based composite hard carbon materials are achieved, and a high-performance composite hard carbon negative electrode material is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551654A_ABST
    Figure CN119551654A_ABST
Patent Text Reader

Abstract

The invention relates to an asphalt-based composite hard carbon material and a preparation method thereof. The hard carbon material is prepared from the following raw materials: asphalt, a solvent A and a solvent B, the preparation method comprises the following steps: crushing the asphalt; then carrying out pre-oxidation crosslinking treatment; then washing and removing impurities; mixing the pre-oxidized asphalt with a solvent A and a solvent B to embed molecules of the solvent A into graphite layers of the pre-oxidized asphalt; then, the asphalt is dried in a segmented drying mode; and finally, carrying out carbonization treatment under an inert protective atmosphere or a vacuum condition, and cooling to room temperature to obtain the asphalt-based composite hard carbon material. Oxidized and crosslinked asphalt is mixed with an embedded solvent, part of solvent molecules are embedded into a graphite microcrystal part of an asphalt material by wet ball milling or soaking, and a carbon layer in a microcrystal region and the content of oxygen-containing functional groups are increased through the embedded solvent, so that a sodium ion diffusion channel is expanded, and the composite material has relatively high reversible specific capacity; and the high-performance composite hard carbon negative electrode material can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy sodium ion secondary battery energy storage devices, and in particular to an asphalt-based composite hard carbon material and a preparation method thereof. Background Art

[0002] Compared with lithium-ion batteries, sodium-ion batteries have significant advantages in raw material supply, cost, low-temperature performance, and safety performance. Due to their unique advantages, sodium-ion batteries are of great significance in promoting energy transformation, improving energy efficiency, enhancing energy security, and promoting technological innovation. With the continuous advancement of technology and the reduction of costs, sodium-ion batteries are expected to play a more important role in the future energy system.

[0003] Hard carbon materials have large interlayer spacing and a porous structure, and are considered to be one of the most ideal negative electrode materials for sodium-ion batteries. The performance of hard carbon negative electrode materials is affected by the precursor and heat treatment process. Among the many precursors, petroleum asphalt, which is mainly composed of thick aromatic hydrocarbons, has a high carbon content, abundant sources, and low prices. However, asphalt is a soft carbon precursor, and the high-temperature carbonization process is easy to graphitize to form a graphite-like structure. The smaller interlayer spacing of graphite affects the embedding or extraction of sodium ions, resulting in poor sodium storage performance of the material. Summary of the invention

[0004] The purpose of the present invention is to address the above-mentioned problems and shortcomings and provide a asphalt-based composite hard carbon material and a preparation method thereof, utilizing the effect of solvent molecules embedding into graphite layers and increasing the interlayer spacing to change the microstructure of asphalt and expand the sodium ion diffusion channel to obtain a high-performance composite hard carbon negative electrode material.

[0005] The technical solution of the present invention is achieved in this way:

[0006] The asphalt-based composite hard carbon material described in the present invention is characterized in that it is made of the following raw materials: asphalt, solvent A and solvent B, wherein the solvent A is one or more combinations of propylene carbonate (PC) and ethylene carbonate (EC), and the solvent B is one or more combinations of methanol, ethanol, isopropanol, acetone, and N-methylpyrrolidone.

[0007] Furthermore, the asphalt is medium-temperature asphalt, mesophase asphalt, petroleum coke or needle coke.

[0008] The method for preparing the asphalt-based composite hard carbon material of the present invention is characterized by comprising the following steps:

[0009] S1. Crush, grind and sieve the raw asphalt to obtain an asphalt precursor with a particle size of ≤20 μm;

[0010] S2. placing the asphalt precursor in a muffle furnace and performing a pre-oxidation and cross-linking treatment in an oxygen-containing atmosphere, and obtaining a pre-oxidized asphalt after cooling. The purpose of the pre-oxidation and cross-linking treatment is to ensure that the asphalt does not dissolve in the subsequent high-temperature carbonization;

[0011] S3, washing the pre-oxidized asphalt with acid and water in sequence to remove impurities in the pre-oxidized asphalt to prevent defects from forming in the later carbonization process, and then drying;

[0012] S4, mixing the preoxidized asphalt treated in step S3 with solvent A and solvent B, and causing the solvent A molecules to embed into the graphite interlayers of the preoxidized asphalt by ball milling or soaking; wherein solvent A is one or more combinations of propylene carbonate (PC) and ethylene carbonate (EC); solvent B is one or more combinations of methanol, ethanol, isopropanol, acetone, and N-methylpyrrolidone; ball milling is to add the preoxidized asphalt treated in step S3 and solvent A and solvent B into a ball mill and mix and ball mill; soaking is to soak the preoxidized asphalt treated in step S3 in a mixed solution of solvent A and solvent B;

[0013] S5, drying the asphalt obtained in step S4 by adopting low-temperature and high-temperature segmented drying methods, wherein the purpose of the low-temperature segment is to remove solvent B for recycling; the purpose of the high-temperature segment is to preliminarily dry and solidify the embedded solvent A molecules;

[0014] S6. Transfer the asphalt obtained in step S5 to a tubular furnace, perform carbonization treatment under an inert protective atmosphere or under vacuum conditions, and obtain an asphalt-based composite hard carbon material after cooling to room temperature.

[0015] Furthermore, the pre-oxidation temperature in step S2 is 200-400° C., and the time is 3-16 hours; the atmosphere includes air, oxygen and ozone.

[0016] Furthermore, the acid solution in step S3 is a mixed aqueous solution of one or more of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, and acetic acid, and the concentration of the acid solution is 0.5 mol / L to 2 mol / L.

[0017] Furthermore, the ball milling in step S4 has a rotation speed of 300 to 500 rpm and a time of 1 to 6 hours.

[0018] Furthermore, the soaking time in step S4 is 6 to 16 hours, and the temperature is 40 to 120°C.

[0019] Furthermore, in step S4, the mass ratio of solvent A to pre-oxidized asphalt is 1:3 to 2:1, and the volume ratio of solvent A to solvent B is 1:10 to 3:5.

[0020] Furthermore, in step S5, the temperature of the low temperature section is 30-70°C, and the temperature of the high temperature section is 80-180°C.

[0021] Furthermore, the temperature of the carbonization treatment in step S6 is 700-1000° C., the heating rate is 3° C. / min-5° C. / min, the time is 1-12 h, and the inert atmosphere is argon or nitrogen.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1. The present invention mixes the oxidatively cross-linked asphalt with an embedding solvent, and embeds part of the solvent molecules into the graphite microcrystal part of the asphalt material by wet ball milling or immersion, thereby increasing the carbon layer of the microcrystal area and the content of oxygen-containing functional groups by the embedding solvent, thereby expanding the sodium ion diffusion channel, making the composite material have a higher reversible specific capacity, and facilitating the acquisition of a high-performance composite hard carbon negative electrode material;

[0024] 2. The carbonization temperature of the present invention is low, only 700-1000°C, which effectively avoids the problem of reduced graphite carbon layer spacing caused by high temperature carbonization, and is energy-saving and environmentally friendly, which is conducive to reducing equipment costs and energy consumption;

[0025] 3. The medium-temperature asphalt used in the present invention is widely available and inexpensive, and the solvents involved are all common low-cost industrial solvents. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 3 and 4 are SEM images of the asphalt-based composite hard carbon materials of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0027] Embodiment 1:

[0028] This embodiment is one of the embodiments of a pitch-based composite hard carbon material and a preparation method thereof described in the present invention. The pitch-based composite hard carbon material prepared by the preparation method can be used as a composite hard carbon negative electrode material. The raw materials and experimental conditions are described in Table 1.

[0029] The preparation method of the asphalt-based composite hard carbon material obtained by this embodiment is as follows:

[0030] S1. Grind the raw asphalt and sieve it to obtain an asphalt precursor with a particle size of ≤20 μm;

[0031] S2. placing the asphalt precursor in a muffle furnace and performing a pre-oxidation cross-linking treatment in an air atmosphere at a pre-oxidation temperature of 350° C. for 6 hours, and obtaining a pre-oxidized asphalt after cooling;

[0032] S3, centrifugally washing the pre-oxidized asphalt three times using 1 mol / L hydrochloric acid solution and deionized water in sequence to remove impurities in the pre-oxidized asphalt, and then drying;

[0033] S4, adding the pre-oxidized asphalt after impurity removal, propylene carbonate (PC) as solvent A, and ethanol as solvent B into a tank for soaking, so as to cause propylene carbonate (PC) molecules to be embedded in the graphite layers of the pre-oxidized asphalt, wherein the volume ratio of propylene carbonate (PC) to ethanol is 1:5, the mass ratio of propylene carbonate (PC) to pre-oxidized asphalt is 3:5, the soaking time is 10 hours, and the soaking temperature is 80°C;

[0034] S5, drying the asphalt obtained by soaking by low temperature and high temperature segmented drying, the drying time is 6 hours, wherein the low temperature segment is 40° C. for removing ethanol, and the high temperature segment is 120° C. for drying and solidifying the embedded propylene carbonate (PC) molecules;

[0035] S6. The segmented dried asphalt is transferred to a tubular furnace. In an argon atmosphere, the temperature is increased from room temperature (25°C) to 900°C at a heating rate of 4°C / min. The asphalt is carbonized at 900°C for 2 hours. After cooling to room temperature, an asphalt-based composite hard carbon material is obtained.

[0036] Embodiment 2-8:

[0037] The raw material composition and preparation conditions for the asphalt-based composite hard carbon material described in Examples 2-8 of the present invention are as described in Table 1.

[0038] Comparative Examples 1-4:

[0039] The asphalt-based composite hard carbon materials and preparation conditions described in Comparative Examples 1-4 are as described in Table 1; the difference between them and the embodiments of the present invention is that if a certain component is absent, the preparation steps containing the component are removed accordingly.

[0040] Table 1 Raw material composition and preparation conditions of Examples 1-8 and Comparative Examples 1-4

[0041]

[0042]

[0043] Material Testing:

[0044] The prepared asphalt-based composite hard carbon material was subjected to XRD test, and the d(002) crystal plane spacing was calculated using the Bragg formula. The results are shown in Table 2.

[0045] Electrochemical performance test:

[0046] Weigh the asphalt-based composite hard carbon material, conductive agent and binder in a mass ratio of 8:1:1, mix and stir to obtain a uniform slurry; apply the uniform slurry on copper foil, dry, roll and cut into a circular electrode with a diameter of 12 mm. Assemble the battery in an argon-filled glove box, use the hard carbon electrode as the positive electrode of the half-cell, the negative electrode is a metal sodium sheet, the diaphragm is a glass fiber diaphragm, and 1.5M NaPF 6 In DMC:EC:EMC=2:1:2Vol%, LIR2032 button battery was prepared. After assembly, it was left to stand at 25℃ for 12h and then heated at 0.1C (1C=330mAg -1 ) was tested between 0.01V and 2.6V, and cycled 100 times. The test results are shown in Table 2.

[0047] Table 2 Structure and performance parameters of Examples 1-8 and Comparative Examples 1-4

[0048]

[0049]

[0050] The present invention optimizes the ratio of solvent A, solvent B and asphalt through a large number of experiments, and develops a preparation process adapted to the preferred formula based on the preferred formula; ultimately, an asphalt-based composite hard carbon material with high specific capacity and excellent cycle performance is prepared.

[0051] As shown in Table 2, compared with the comparative example 1 without adding solvent A, the examples 1-8 with adding solvent A have a larger d(002), that is, the examples have a larger interplanar spacing, which is conducive to the embedding of sodium ions into the microcrystalline graphite layer. Figure 1 It can be seen that an obvious graphite layer can be observed at the edge of the particles of Example 1, which is a slight peeling phenomenon of the graphite layer caused by the embedding of solvent A into the microcrystalline graphite layer. The edges of the particles of Comparative Example 1 without adding solvent A are smooth and delicate.

[0052] Comparing Examples 1-8 and Comparative Examples 1-2, it can be seen from their reversible specific capacities that the hard carbon material with the addition of solvent A has a higher reversible specific capacity, whether by immersion or ball milling. As can be seen from Table 2, for Comparative Examples 1, 3, 6, 7 and Comparative Example 4, when the volume ratio of solvent A to solvent B is the same, the reversible specific capacity increases as the proportion of solvent A increases. Comparing the reversible specific capacities of Example 7 and Comparative Example 4, when the proportion of solvent A increases to a certain extent, increasing the amount of solvent A does not significantly increase the reversible specific capacity of the material. Therefore, the appropriate mass ratio of solvent A to pre-oxidized asphalt is 1:3 to 2:1.

[0053] As can be seen from Table 2, when comparing Examples 2, 3, 4, 5 and Comparative Example 3, the ratio of solvent A to pre-oxidized asphalt is the same, the ratio of solvent A to solvent B will affect the electrochemical performance of asphalt-based composite hard carbon. The volume ratio of solvent A to solvent B is less than 1:10, which easily wastes volatile solvent B. Comparing the reversible specific capacity of Examples 2, 3, 4, 5 and Comparative Example 3, when the volume ratio of solvent A to solvent B reaches 4:5, the solution concentration is too large, which affects the embedding effect of solvent A, resulting in a decrease in the reversible specific capacity. Therefore, the appropriate volume ratio of solvent A to solvent B is 1:10 to 3:5.

[0054] In addition, in other embodiments of the present invention, the raw materials and various parameters required for preparing the asphalt-based composite hard carbon material can also be selected from other raw materials and values ​​that meet the requirements. For example: ethylene carbonate (EC) can also be used as solvent A; or, a mixture of propylene carbonate (PC) and ethylene carbonate (EC) can be used as solvent A; and solvent B can also be one or more combinations of methanol, isopropanol, acetone, and N-methylpyrrolidone. When ball milling is used for mixing, the pre-oxidized asphalt after impurity removal and solvent A and solvent B are added to the ball mill jar for mixed ball milling, and the speed of the ball mill is controlled within the range of 300 to 500 rpm and the time is within the range of 1 to 6 hours; when soaking mixing is used, as long as the soaking time is within the range of 6 to 16 hours and the temperature is within the range of 40 to 120°C. Moreover, other values ​​can be selected for the parameters of pre-oxidation, as long as the temperature is within the range of 200 to 400°C and the time is within the range of 3 to 16 hours; the atmosphere can also be oxygen and ozone, and it is ensured to be an oxygen-containing atmosphere. The acid solution used for washing and removing impurities can also be a mixed aqueous solution of one or more of sulfuric acid, phosphoric acid, nitric acid, and acetic acid, and the concentration of the acid solution can be in the range of 0.5mol / L to 2mol / L. In the staged drying process, as long as the temperature of the low temperature section is in the range of 30 to 70°C and the temperature of the high temperature section is in the range of 80 to 180°C. In the carbonization process, as long as the carbonization temperature is in the range of 700 to 1000°C, the heating rate is in the range of 3°C / min to 5°C / min, the carbonization time is in the range of 1 to 12h, and the inert atmosphere can also be nitrogen. Of course, the carbonization process can also be carried out under vacuum conditions. Asphalt as a precursor can be selected from medium-temperature asphalt, mesophase asphalt, petroleum coke or needle coke.

[0055] The present invention is described by way of embodiments, but does not constitute a limitation to the present invention. With reference to the description of the present invention, other changes to the disclosed embodiments are easily conceivable to professionals in the field, and such changes should fall within the scope defined by the claims of the present invention.

Claims

1. A pitch-based composite hard carbon material, characterized in that The invention is made of the following raw materials: asphalt, solvent A and solvent B, wherein the solvent A is one or more combinations of propylene carbonate (PC) and ethylene carbonate (EC), and the solvent B is one or more combinations of methanol, ethanol, isopropanol, acetone and N-methylpyrrolidone.

2. The pitch-based composite hard carbon material according to claim 1, characterized in that: The asphalt is medium-temperature asphalt, mesophase asphalt, petroleum coke or needle coke.

3. A method for preparing a pitch-based composite hard carbon material, the method being used to prepare the pitch-based composite hard carbon material as claimed in any one of claims 1 to 2, characterized in that The following steps are involved: S1. Crush, grind and sieve the raw asphalt to obtain an asphalt precursor with a particle size of ≤20 μm; S2, placing the asphalt precursor in a muffle furnace, performing a pre-oxidation cross-linking treatment in an oxygen-containing atmosphere, and obtaining a pre-oxidized asphalt after cooling; S3, washing the pre-oxidized asphalt with acid solution and water in sequence to remove impurities in the pre-oxidized asphalt, and then drying; S4, mixing the preoxidized asphalt treated in step S3 with solvent A and solvent B, and causing the solvent A molecules to embed into the graphite interlayers of the preoxidized asphalt by ball milling or soaking; wherein solvent A is one or more combinations of propylene carbonate (PC) and ethylene carbonate (EC); solvent B is one or more combinations of methanol, ethanol, isopropanol, acetone, and N-methylpyrrolidone; ball milling is to add the preoxidized asphalt treated in step S3 and solvent A and solvent B into a ball mill and mix and ball mill; soaking is to soak the preoxidized asphalt treated in step S3 in a mixed solution of solvent A and solvent B; S5, drying the asphalt obtained in step S4 by adopting low-temperature and high-temperature segmented drying methods, wherein the purpose of the low-temperature segment is to remove the solvent B, and the purpose of the high-temperature segment is to preliminarily dry and solidify the embedded solvent A molecules; S6. Transfer the asphalt obtained in step S5 to a tubular furnace, perform carbonization treatment under an inert protective atmosphere or under vacuum conditions, and obtain an asphalt-based composite hard carbon material after cooling to room temperature.

4. The method for preparing the pitch-based composite hard carbon material according to claim 3, characterized in that: The pre-oxidation temperature in step S2 is 200-400° C., and the time is 3-16 hours; the atmosphere includes air, oxygen and ozone.

5. The method for preparing the asphalt-based composite hard carbon material according to claim 3, characterized in that: The acid solution in step S3 is a mixed aqueous solution of one or more of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, and acetic acid, and the concentration of the acid solution is 0.5 mol / L to 2 mol / L.

6. The method for preparing the pitch-based composite hard carbon material according to claim 3, characterized in that: The ball milling in step S4 has a rotation speed of 300 to 500 rpm and a time of 1 to 6 hours.

7. The method for preparing the pitch-based composite hard carbon material according to claim 3, characterized in that: The soaking time in step S4 is 6 to 16 hours, and the temperature is 40 to 120°C.

8. The method for preparing the pitch-based composite hard carbon material according to claim 3, characterized in that: In step S4, the mass ratio of solvent A to pre-oxidized asphalt is 1:3 to 2:1, and the volume ratio of solvent A to solvent B is 1:10 to 3:

5.

9. The method for preparing the pitch-based composite hard carbon material according to claim 3, characterized in that: In step S5, the temperature of the low temperature section is 30-70°C, and the temperature of the high temperature section is 80-180°C.

10. The method for preparing the pitch-based composite hard carbon material according to claim 3, characterized in that: The temperature of the carbonization treatment in step S6 is 700-1000° C., the heating rate is 3° C. / min-5° C. / min, the time is 1-12 hours, and the inert atmosphere is argon or nitrogen.

Citation Information

Cited By

  • Preparation method of hard carbon material with improved high rate capability for sodium ion battery

    CN120246983A